The study of constructing evaluation indicators for the implementation of employee assistance programs in public sectors - Chen, Yin-Che; Chung, Su-Ching; Chu, Hui-Chuang (Frontiers in Psychology, 2024)
Employee assistance programs require resources and manpower of various natures across different types of public sector organization. This study began by outlining elements for comparing employee assistance programs' evaluation criteria in four types of public sector organization on the basis of 22 service measures for such programs implemented by the Ministry of Labor in relation to three major aspects: work, life, and health. Elements of the evaluation criteria for public sector employee assistance programs were determined by surveying a panel of experts using the modified Delphi method. Last, the weight associated with the elements of evaluation criteria were calculated using the fuzzy analytic hierarchy process, and the criteria of four types of public sector organization were explored. Data analysis indicated that the weight and priorities associated with elements of evaluation criteria for EAPs implemented by four types of public sector organization were not fully identical. The results of this study suggest that, in terms of EAPs, the Directorate-General of Personnel Administration of the Executive Yuan should be pursuant to appropriate employee assistance programs provided by various public sector organizations according to the needs of their employees as well as the diverse objective conditions in which these organizations operate.